Choices of Virtue and Vice Products and Their Impact on Visual Attention: A Meta-Analysis of Eye-Tracking Food Research - Ladeira WJ; Lim WM; Perin MG; de Oliveira Santini F; Rasul T; Gursoy D; Hall CM; Akhtar S (John Wiley and Sons Ltd, 2025)
This article aims to analyze the impact of attention drivers associated with food bottom-up processes (virtue, vice, and binary choices) on physiological measures (fixation count and fixation duration) of psychological constructs (attention allocation and cognitive processing) of visual attention. Existing studies have analyzed these relationships in an isolated and scattered manner, indicating the need for a new study that integrates the effect sizes to better understand the state of the art. To achieve this goal, a meta-analysis was carried out, compiling information from 54 articles, encompassing 21,756 participants and 153 effect sizes (Cohen's d), to discern patterns of attention allocation and cognitive processing across three product choice scenarios: choice of virtue food products, choice of vice food products, and choice of their combination. The results reveal that virtue and vice choice contexts influence attention allocation while virtue and binary choice contexts influence cognitive processing. The results also show that the heterogeneity of the effects of virtue, vice, and binary choice contexts can be explained by externally driven marketing factors such as the cause of allergy or intolerance (product), shopping channel (place), and vividness of product presentation (promotion), as well as internally driven socioeconomic indicators such as average supply of fat per day (health), average supply of food calories per day (health), body mass index (health), expenditure on food and non-alcoholic beverages (economic), and reading PISA score (education).
Keywords: eye-tracking; meta-analysis; product choice; vice; virtue; visual attention